Design and Implementation of an Online Thesis Management System Using the Waterfall Model at a Health Polytechnic in Indonesia - Alsri Windra Doni; Darwel; Mahdalena Prihatin Ningsih; Ponda, Aprizal; Sugriarta, Evino; Dewi Susanti (Indonesian Journal of Learning Education and Counseling, 2026)
The study aims to develop and validate an online thesis management system designed to address the limitations of manual systems in the thesis supervision process, such as a lack of transparency, delays in communication, and difficulties in monitoring student progress. In response to these challenges, this study proposes an integrated system framework that facilitates real-time academic interaction between students and their thesis advisors. The method employs a system development research approach using the waterfall model, which was selected for its suitability in developing structured and systematically documented systems. The research phases include requirements analysis, system design based on Entity Relationship Diagrams (ERDs) and use case diagrams, implementation, and system testing. The system was evaluated using a usability testing approach, involving the distribution of a questionnaire to 55 respondents to measure usability, ease of use, and user satisfaction. The results indicate that the developed system model is capable of improving the efficiency of thesis supervision management, enhancing the transparency of academic processes, and supporting data driven decision making. The main contribution of this study lies in the development of an adaptive, user-oriented academic information system model, which not only has practical implications for the management of final projects but also provides a conceptual foundation for the development of similar systems in higher education institutions. The implications of this study underscore the importance of ongoing system integration with other academic platforms, as well as the need for periodic system evaluations to enhance the user experience and ensure the sustainability of the implementation.